2019
DOI: 10.26479/2019.0502.34
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An efficient micropropagation protocol from shoot tip explants of Mucuna pruriens, an annual leguminous climber was established. Shoot tip excised from seven days old aseptically grown seedlings were inoculated on Murashige and Skoog (MS 1962) medium containing different concentration of benzyladenine (BA) alone or in combination with an auxins (NAA, IBA, IAA) for multiple shoot induction. BA (2.5 μM) was found to be optimum for inducing maximum shoots (7.67 ± 0.33) per explant. The augmentation of auxins in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Sucrose was shown to play a vital role in improving plant growth and shoot regeneration rate, while glucose and maltose played a minor role in shoot induction. The findings in the current study are consistent with previous studies which reported that sucrose induced shoot formation of Soybean [66], Velvet bean [67], Peach [68], Gotu Kola [16], Pea [69,70], Kris [71], Cucumber [72]. The types of carbohydrate sources, and their concentrations may influence culturing success [63,65].…”
Section: Discussionsupporting
confidence: 92%
“…Sucrose was shown to play a vital role in improving plant growth and shoot regeneration rate, while glucose and maltose played a minor role in shoot induction. The findings in the current study are consistent with previous studies which reported that sucrose induced shoot formation of Soybean [66], Velvet bean [67], Peach [68], Gotu Kola [16], Pea [69,70], Kris [71], Cucumber [72]. The types of carbohydrate sources, and their concentrations may influence culturing success [63,65].…”
Section: Discussionsupporting
confidence: 92%